KEKERASAN ALA KAPITALISME Sebuah Telaah atas Buku Violence and Democratic Society - Alami, Athiqah Nur (Jurnal Penelitian Politik, 2016)
The rise of capitalism at the present does not mark it as a glorious ideology. Capitalism has many dark sides that we should aware. One of the dark sides that is worth to be noticed is the emergence of violence against human that happened to maintain the existence of Capitalism itself The Violence has various forms, direct violence and indirect violence. Each form of the violence brings conseguence that is often disrespect the universal human rights.